(untitled) (Acta Scientiarum. Technology, 2016)
The goal of this study was to apply the Mann-Kendall test to the rainfall data of eight macroregions of the Ceará State aiming to determine climate trends in their time series. To this end were used rainfall data obtained by the FUNCEME for the period 1974-2011. The Mann-Kendall test was applied to verify trends in rainfall series, and the Students´s t-test to check significant differences in the trend values. Downward trends in annual rainfall were found for the metropolitan region of Fortaleza, Sertão dos Inhamuns and Sertão Central, areas that also presented smaller green areas and/or fewer vegetated areas. Upward trends in rainfall were observed on the West Coast, Sobral/Ibiapaba, Baturité, East Coast/ Jaguaribe and Cariri/South Central. Â